Analysis of Demographic Transitions in Global Population - A. Ibrahim, Nathier (Opción, 2019)
The demographic growth in the seventeenth century and population growth rates increased until the end of the 20th century. It was the first time to de- termine fertility in Europe, followed by other countries such as Japan, East Asian countries and other countries that wished to find a balance between population growth and the growth of other complementary sectors. These de- mographic changes led to the re-shaping of the different sectors of population, especially the economic ones. However, most of the third world countries have continued to grow their population, which has generated many economic and social problems. This has been accompanied by security and political unrest and the illegal immigration of their youth, which has directly affected the sys- tems and laws of the immigrant countries. We used in this study, the United Nations publications on demographic changes, their presentation and analy- sis, as well as the use of some statistical equations, were adopted.